Effects of a very congested match schedule on body-load impacts, accelerations, and running measures in youth soccer players - Arruda, A. F. S.; Carling, C.; Zanetti, V.; Aoki, M. S.; Coutts, A. J.; Moreira, A (International Journal of Sports Physiology and Performance, 2015)
Purpose: To analyze the effects of a very congested match schedule on the total distance (TD) covered, high-intensity-running (HIR) distance, and frequency of accelerations and body-load impacts (BLIs) performed in a team of under-15 soccer players (N = 10; 15.1 ± 0.2 y, 171.8 ± 4.7 cm, 61 ± 6.0 kg) during an international youth competition. Methods: Using global positioning systems, player performances were repeatedly monitored in 5 matches performed over 3 successive days. Results: Significant differences were observed between matches (P < .05) for the frequency of accelerations per minute, BLIs, and BLIs per minute. No differences were observed for the TD covered, TD run per minute, number of high-intensity runs, distance covered in HIR, per-minute peak running speed attained, or frequency of accelerations. The frequency of accelerations per minute decreased across the competition while BLIs were higher during the final than in all other matches. Conclusions: These results suggest that BLIs and acceleration might be used as an alternative means to represent the external load during congested match schedules rather than measures related to running speed or distance covered.